Immunomodulatory effect of Neem (Azadiracta indica) Extract on Recovery and Conception Rate in Infectious Repeat Breeder Crossbred Cows - Bhardwaz, Anavil; Nema, S.P.; Mahour, S.S.; Chabbra, Daljeet; Aich , R.; Kumar, Sudarshan (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was undertaken to evaluate the therapeutic efficacy of Neem (Azadiracta indica) extract in 20 infectious repeat breeder crossbred cows. Animals were divided into two groups of ten in each. The animals in first group were treated with 15% concentration of Neem extract w/v dissolved in saline to make 30 ml, Intra Uterine at 24 hrs intervals for 7 days, while the animals in control group were infused with 30 ml saline for 7 days. Bacterial count in uterine flushing declined significantly (p
Keywords: Repeat breeder; Uterine flushing; Neem extract; Bacterial count; PMNs %; Whiteside test; Conception rate